Pengaruh Gaya Mengajar Guru terhadap Motivasi Belajar Siswa Sekolah Dasar SDN Nyapah 3 - Nurul Hasanah; Desty Endrawati Subroto; Azzahra Vindri Farida; Listaria Agustin; Ifatul Jahro; Rahmi Kurnia (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study investigates how teaching methods affect students' willingness to learn. Students' interest and engagement in the learning process can be enhanced by effective teaching methods. Different teaching philosophies, including collaborative, inventive, interactive, and authoritative, have varying effects on students' willingness to learn. To achieve the best learning outcomes, it is necessary to choose a teaching style that suits the needs and characteristics of students. In this study, a qualitative approach was used to analyze students' perceptions of various teaching styles in the classroom environment. The results showed that interactive and collaborative methods tend to increase learning motivation more than the one-way authoritative style. In addition, teacher emotional involvement, the use of interesting learning media, and a conducive classroom atmosphere also contribute greatly to shaping students' learning interests. These findings are expected to be a reference in designing more adaptive and effective teaching strategies.